2018
DOI: 10.1186/s12870-018-1359-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effect of 24-epibrassinolide and silicon alleviates cadmium stress via the modulation of antioxidant defense and glyoxalase systems and macronutrient content in Pisum sativum L. seedlings

Abstract: BackgroundThis study assessed the effects of 24-epibrassinolide (EBL, 10–7M) and silicon (2 mM) on the alleviation of cadmium (Cd, 150 mg L–1) toxicity in Pisum sativum L. seedlings via the modulation of growth, antioxidant defense, glyoxalase system, and nutrient uptake.ResultsShoot and root lengths declined by 46.43% and 52.78%, respectively, following Cd stress. Shoot and root dry weights also declined with Cd toxicity. Biochemical and physiological aspects exhibit significant decline including total chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
71
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(78 citation statements)
references
References 120 publications
(96 reference statements)
6
71
0
1
Order By: Relevance
“…The inclusion of VA in the growth medium increased both the Gly I and Gly II enzyme activity, thus reducing the MG content and providing the seedlings with tolerance against MG-induced glycation as well as oxidative stress. The results of the present study are corroborated by those of other researchers who reported phytoprotectant-induced increases in the Gly enzyme activity and concomitant reduction in MG content [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…The inclusion of VA in the growth medium increased both the Gly I and Gly II enzyme activity, thus reducing the MG content and providing the seedlings with tolerance against MG-induced glycation as well as oxidative stress. The results of the present study are corroborated by those of other researchers who reported phytoprotectant-induced increases in the Gly enzyme activity and concomitant reduction in MG content [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…Sheng et al [65] have demonstrated increased uptake of K and Ca due to SA in wheat, resulting in the up-regulation of antioxidant system and mitigation of oxidative effects under manganese stress. Increased uptake of mineral nutrients influences the cellular functioning and whole plant performance by regulating processes like photosynthesis, antioxidant systems, and enzyme activity [42,66]. In salt-stressed cucumber, foliar application of SA has been reported to mitigate the reduction in uptake of key macro and microelements.…”
Section: Discussionmentioning
confidence: 99%
“…Plants grown under salinity stress show common symptoms or physiological responses due to the accumulation of toxic levels of ions (Na + , Cl − , and SO 2 − ) in the cells, leading to nutritional and osmotic imbalances, and water use insufficiency (Hasegawa et al, 2000;Kim et al, 2014a;Shu et al, 2017;Rehman et al, 2019). Moreover, reactive oxygen species (ROS), such as the superoxide anion (•O 2 − ), hydroxyl radicals (•OH − ), and hydrogen peroxide (H 2 O 2 ), accumulate in salt-stressed plants (Kim et al, 2014a;You and Chan, 2015;Jan et al, 2018;Ahmad et al, 2019). Ultimately, the plant cell walls collapse, causing the plant cells to die (Shu et al, 2017;Rehman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%